THE SCIENTIFIC PRODUCTION ABOUT THE SCHOOL PHYSICAL EDUCATION IN BRAZIL: ANALYSIS OF THE STUDIES PRESENTED IN THE NATIONAL SYMPOSIUM OF PHYSICAL EDUCATION (Fiep Bulletin - online, 2014)
The subject " school " is, certainly, one of the more studied in the physical education. A fast rising, of the works in events presented by Brazil, it ratifies this statement. This research has as objective accomplishes an analysis of the documents of the 25 editions of the Simposio Nacional de Educação Física, promoted by the Escola Superior de Educação Física of the Universidade Federal de Pelotas, identifying the exposed studies for the participants and guests of the event in the extent of the school physical education. This study is of the bibliographical type, whose main sources of rising of the information were the annals and the collections of the event. The choice of those documents happened because they are them that synthesize all the organization of the event and, in that way, they translate the themes and actions that were prioritized in each one of the editions. The group of works analyzed in the 25 editions of the Simposio Nacional de Educação Física, expresses a little of that that was produced in the area of the school physical education in the last three decades. It identified that some themes that today they are concern source in the area, they have already been studied from the first editions of the Symposium that reveals that the problems because it passes the physical education are not new, but they are quite current. That indicates that the education politics implemented in the last decades have not been capable to minimize the problems faced by the teachers in the public school. Already some themes as the physical education in the night teaching, the subjects regarding the administration of the school and the rural way were not white of studies in the 25 analyzed editions.
Keywords: school; physical education; research